Mycobacterium tuberculosis GrpE, A Heat-Shock Stress Responsive Chaperone, Promotes Th1-Biased T Cell Immune Response via TLR4-Mediated Activation of Dendritic Cells - Kim, Woo Sik; Jung, In Duk; Kim, Jong-Seok; Kim, Hong Min; Kwon, Kee Woong; Park, Yeong-Min; Shin, Sung Jae (Frontiers in Cellular and Infection Microbiology, 2018)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis, is an extremely successful pathogen with multifactorial ability to control the host immune response. Insights into the Mtb factors modulating host response are required for the discovery of novel vaccine antigen targets as well as a better understanding of dynamic interactions between the bacterial factors and host cells. Here, we exploited the functional role of Mtb GrpE, a cofactor of heat-shock protein 70 (HSP70), in promoting naïve CD4+/CD8+T cell differentiation toward Th1-type T-cell immunity through interaction with dendritic cells (DCs). GrpE functionally induced DC maturation by up-regulating the expression of cell surface molecules (CD80, CD86, and MHC class I and II) and production of several pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-12p70) in DCs. These effects of GrpE in DC activation were initiated upon binding to Toll-like receptor 4 (TLR4) followed by activation of downstream MyD88-, TRIF-, MAPK-, and NF-κB-dependent signaling pathways. GrpE-activated DCs displayed an excellent capacity to effectively polarize naïve CD4+ and CD8+ T cells towards Th1-type T-cell immunity with the dose-dependent secretion of IFN-γ and IL-2 together with increased levels of CXCR3 expression. Notably, GrpE-stimulated DCs induced the proliferation of GrpE-specific Th1-type effector/memory CD4+/CD8+CD44highCD62Llow T cells from the spleen of Mtb-infected mice in a TLR4-dependent manner. Collectively, these findings suggest that GrpE is a novel immune activator that interacts with DCs, in particular, via TLR4, to generate Th1-biased memory T cells in an antigen-specific manner. GrpE may contribute to the enhanced understanding of host-pathogen interactions as well as providing a rational basis for the discovery of new potential targets to develop an effective tuberculosis vaccine.